Optimal Channel Strategy for Dual-Channel Retailers: The Bright Side of Introducing Agency Channels - Wang, Yang (Frontiers in Physics, 2022)
Driven by the prosperity of the online retail market and the success of the agency selling format, dual-channel retailers have engaged extensively in online retailing. However, whether dual-channel retailers act as intermediaries to introduce agency channels for third-party sellers in their online stores has not yet received sufficient attention. To address this problem, we perform game-theoretic analysis of the optimal channel strategy of a dual-channel retailer under three channel structures: No-agency mode, manufacturer-agency mode, and e-tailer-agency mode. Under each structure, the price competition model is studied, with the manufacturer as the Stackelberg leader and the retailer or authorized e-tailer as the follower. We analyze the optimal prices and profits of different structures and study the influence of agency channels. Our analysis shows that when the commission rate is higher than a certain threshold, the dual-channel retailer will introduce an agency channel for the third-party seller, and when the commission rate is high, the dual-channel retailer prefers to introduce an agency channel for the manufacturer rather than an authorized e-tailer. However, higher offline operating cost reduces the willingness of the dual-channel retailer to introduce an agency channel. Furthermore, the manufacturer will always benefit from the agency channel and, because of the mitigation of double marginalization, the manufacturer is most profitable in the manufacturer-agency mode. Finally, introducing an agency channel for the third-party seller can create a “win-win” outcome for the manufacturer and the dual-channel retailer, while the e-tailer-agency mode can increase the dual-channel retailer’s relative channel power under certain conditions.